Core‐Shell Nano‐Cobalt Catalyzed Chemoselective Reduction of N‐Heteroarenes with Ammonia Borane. Issue 23 (4th November 2022) - Chen, Sanxia; Xue, Wenxuan; Tang, Conghui
Abstract: An easily prepared core‐shell heterogeneous nanocobalt catalyst was reported, which could achieve selective reduction of N‐heteroarenes with ammonia borane under mild conditions and ambient atmosphere. Various quinoline, quinoxaline, naphthyridine, isoquinoline, acridine, and phenanthroline derivatives were hydrogenated with high selectivity and efficiency. Notably, substrates bearing sensitive functional groups under molecular hydrogen reduction conditions, such as cyano, ester, and halogens were well tolerated by the catalytic system. Moreover, with our novel method several bioactive molecules were prepared. Also, this catalyst could be applied in the liquid organic hydrogen storage system by reversible hydrogenation and dehydrogenation of heteroarene in high efficiencies. Abstract : Awesome to the core : A core‐shell nano‐cobalt catalyst was reported for the chemoselective reduction of N‐heteroarenes with ammonia borane under mild conditions, various N‐heteroarenes including bioactive compounds were hydrogenated smoothly, and reduction sensitive functional groups such as cyano, ester, and halogens were well‐tolerated. This novel method was applied in the synthesis of medicinally important molecules and organic hydrogen storage system as well.